Business Model Design of a Digital-Based Outfit Recommendation Application for Fashion Personalization - Wahyudi, Nayla Nakeisha; Ariyani Mutiah Safitri; Darmadi, Anastasia Bella Clarisa; Ridho Aulia Rihhadatul Hudai; Petrus Sokibi (Primakara University, 2026)
The rapid development of the digital fashion industry has increased the demand for personalization in outfit and makeup selection, particularly among Generation Z and millennial women who face time constraints and demonstrate growing awareness of sustainability. Common issues include difficulties in matching clothing according to personal characteristics, low self-confidence due to inappropriate outfit choices, and a tendency toward overconsumption influenced by fast fashion practices. This study aims to design a business model and develop a user interface prototype for the ColorMatch application as an AI-based outfit recommendation platform, utilizing the Business Model Canvas (BMC) framework and the Prototyping development method. A descriptive qualitative approach is employed to analyze the nine elements of the BMC, while the prototyping stages include requirement identification, wireframe design, mockup development, and feedback-based evaluation to produce a user-oriented UI/UX design. The results indicate that ColorMatch offers a value proposition in the form of outfit and makeup recommendations based on seasonal color analysis, mood-based styling, and personal wardrobe optimization. The integration of digital business model approaches, AI technology, and UI/UX design through prototyping results in a platform that is economically viable, responsive to user needs, and supportive of sustainable fashion practices.